FORMULASI KAPSUL ANTIDIABETES EKSTRAK UMBI BAWANG DAYAK (Eleuhterine palmifolia (L) Merr.) DENGAN VARIASI KONSENTRASI AVICEL 101 DAN PREGELATINIZED STARCH - Indriawan, Kadek Agus; Sa'adah, Hayatus; Helmidanora, Rusdiati (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Diabetes Mellitus is a heterogeneous disease characterized by improvement glucose levels in the blood. Several studies have shown that Dayak onions have hypoglycemic activity or lowering blood glucose levels which may be very useful for treatment of diabetes mellitus. Flavonoids contained in Dayak onions are in position to restore the characteristics of pancreatic tissue by increasing insulin release through β cells, so that it can lower blood sugar levels and can also increase sensitivity peripheral cells to insulin. Given the great potential of Dayak onions as antidiabetic, it is very important to develop more practical preparations that can carrying out weight uniform measurements of the products used, of course, one of them is in pharmaceutical preparations capsule form. This examination aims to determine the physical properties and antioxidant activity of Dayak onion extract capsules in large quantities concentration of Avicel PH 101 and pregelatinized starch as fillers. Look was carried out experimentally using three formulas with various concentrations fillers with a ratio between Avicel PH 101 and pregelatinized starch, in particular formula I (1:0), formulation II (0.5:0.5) and method III (0:1). body residence and drug stability is checked and then tested for antioxidant hobby spectrophotometric use. The research results show that the formula with the composition of Avicel PH 101 and pregelatinized starch in the ratio (0:1) is given the best wet house physical test results were 3.4%, sliding houses 12.82 gram/second, angle of repose 29.85⁰, compressibility 8%, density 0.544 and destroyed time 3 minutes 37 seconds. along with antioxidant effects activity examination showed that the drug Dayak onion extract proved to be moderate antioxidant activity, specifically 228.78 ppm.